A Pilot Study Comparing Hysteroscopic Adhesiolysis by Conventional Resectoscope Versus Mini-resectoscope - Kallol Kumar Roy; Archana Lingampally; Yamini Kansal; Juhi Bharti,; Sunesh Kumar; Perumal Vanamail; Seema Singhal; Jyoti Meena (Oman Medical Journal, 2017)
Objectives: To compare the feasibility and efficacy of the mini-resectoscope with the conventional resectoscope in terms of the operative, menstrual, and reproductive outcome in hysteroscopic adhesiolysis in infertile women. Methods: We conducted a parallel prospective randomized study at All India Institute of Medical Sciences, New Delhi. A total of 60 patients underwent hysteroscopic adhesiolysis using either conventional resectoscope (n = 30) or mini-resectoscope (n = 30). The primary outcome measures were pregnancy-related indicators. Secondary outcome measures were the operative parameters (cervical dilatation time, operation time, postoperative pain scores, fluid deficit, and preoperative and postoperative sodium levels), second-look hysteroscopy findings, and improvement in the menstrual pattern after surgery. Results: Cervical dilatation time and pain score 30 minutes after the procedure were significantly lower in the mini-resectoscope group. Out of the total 21 cases with hypomenorrhea, 12 cases (57.1%) started having normal menstrual flow postsurgery. All amenorrheic patients resumed menstruation after surgery. However, nine cases continued to have hypomenorrhea. Over long-term follow-up, 16 patients out of 60 had conceived (seven in the conventional resectoscope group and nine in the mini-resectoscope group). There were three ongoing pregnancies, three abortions, one ectopic pregnancy, and nine term pregnancies. The difference between the two groups was not statistically significant. Conclusions: The use of mini-resectoscope for hysteroscopic adhesiolysis is associated with reduced operative morbidity. Use of the mini-resectoscope is an effective and safe alternative to the conventional system.